2015
DOI: 10.17221/8179-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

A simplified duplex real-time PCR incorporating TaqMan minor groove binder (MGB) probes and an exogenous internal positive control for the simultaneous detection of Mycoplasma gallisepticum and Mycoplasma synoviae cultures

Abstract: Mycoplasma gallisepticum (MG) and Mycoplasma synoviae (MS) are the most pathogenic and economically important mycoplasma pathogens that infect chickens. The development of rapid and innovative molecular diagnostic techniques is of pivotal importance for their effective control. The aim of the present study was to develop a novel duplex TaqMan real-time PCR assay for the simultaneous detection of MG and MS. This duplex real-time PCR assay incorporates TaqMan (FAM/NED) labelled minor groove binder (MGB) probes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…A higher sensitivity detection (lower CT values) was achieved with the TaqMan FAM TM reporter dye in this study. Others (Ehtisham-ul-Haque et al, 2015) have reported the results for FAM to be stronger that those obtained with the NED TM reporter dye. Additionally, the low detection value of NED as a reporter dye is well corroborated in past experience.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…A higher sensitivity detection (lower CT values) was achieved with the TaqMan FAM TM reporter dye in this study. Others (Ehtisham-ul-Haque et al, 2015) have reported the results for FAM to be stronger that those obtained with the NED TM reporter dye. Additionally, the low detection value of NED as a reporter dye is well corroborated in past experience.…”
Section: Discussionmentioning
confidence: 89%
“…Traditionally, diagnosis of MG infection in the poultry industry depended upon serological screening such as serum plate agglutination (SPA) and enzyme-linked immunosorbent assay (ELISA) hemagglutination inhibition (HI), which historically are considered the most reliable tools for identifying subclinical infection in the flock (Barua et al, 2006;Purswell et al, 2012;Kaboli et al, 2013); however, they sometimes lack the required specificity and sensitivity (Carli, and Eyigor, 2003;Kaboli et al, 2013). Therefore, in the last decade, rapid polymerase chain reaction (PCR) methods with high specificity and sensitivity for MG have been very useful for laboratory diagnosis of infected birds (Ehtisham-ul-Haque et al, 2015;Raviv and Kleven, 2009). Polymerase chain reaction based on identification of the mgc2-cytadhesin encoding surface protein gene for MG is the most widely used methods for the detection, typing and determination of the source of infection (Gerchman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations